PENGGUNAAN MEDIA KOMIK DIGITAL INTERAKTIF UNTUK MENINGKATKAN BERCERITA SISWA KELAS IV MADRASAH IBTIDAIYAH DARUSSALAM JELUTUNG - Karlina, Pitri; Tabroni; Nisa Aulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The goal of this study was to determine how fourth-grade students at Madrasah Ibtidaiyah Darussalam Jelutung may enhance their communication abilities through the use of interactive digital comic media. 27 fourth-grade students from MI Darussalam Jelutung participated in this study, which employed the Classroom Action Research (CAR) approach. Interviews, observations, tests, and documentation procedures were employed as data gathering methods for this study in accordance with the research methodology. In the meantime, both quantitative and qualitative methodologies were used in data analysis. The four components of the Kemmis & McTaggar design model—planning, implementation, observation, and reflection—were applied in this investigation. There were two cycles to this study, each with two meetings. According to the study, fourth-grade students at MI Darussalam Jelutung can improve their storytelling skills by using interactive digital comics. With 54% of students finishing cycle I, the average score rose to 68%, and with 85% of students finishing cycle II, it reached 82%. Interactive digital comic media may help fourth-grade pupils at MI Darussalam Jelutung in Jambi City develop their narrative abilities.